Assessment of the impact of sediment dispersion on coral reef ecosystems caused by submarine cable installation in the Con Dao Archipelago, Vietnam - Vu, Van Lan; Lan, Nguyen Hong (Vietnam Journal of Marine Science and Technology, 2025)
This study evaluated the impact of sediment dispersion from submarine cable installation on coral reef ecosystems in Con Dao Archipelago, Vietnam using the MIKE 3 hydrodynamic model. It analyzed coral reef distribution and turbidity spreading under different monsoon conditions. Results showed that during the Northeast monsoon, turbidity primarily affected the southern island regions with few coral reefs, while the Southwest monsoon caused significant impacts on reefs along the western coast, especially near Hon Tre Lon and Hon Troc Islands along the cable route. Maximum turbidity concentrations were recorded at 0.00028 kg/m³ (surface), 0.0033 kg/m³ (mid-depth), and 0.12 kg/m³ (near-seabed), with an impact radius of 3 km. Coral reefs along the east coast and Hon Bay Canh Island were minimally affected. These findings suggest that cable installations should occur during the Northeast monsoon to mitigate ecological impacts.